Adolescentes em situação de vulnerabilidade social: vínculos, modos de ser e viver - Elifilete Costa Araújo Pena (2019)
The purpose of the present study is to advance understanding adolescents, in the context of social vulnerability and their experiences in the territory. This is an exploratory research of qualitative nature, whose data collection was performed through narrative interviews with adolescents referred at the Reference Centers of Social Assistance (CRAS) in Nova Lima (MG). In order to reach the objective of mapping the boundary spaces in the territory, cartography was used to construct the maps. The field note was also used to help identify important points during the data collection, composing the basis for the analysis. The city is marked by social inequalities, and some places are characterized by social vulnerability, creating a favorable scenario for weakening bonds and limiting the relational field, susceptibly leaving adolescents exposed to risks. To interpret the results, we used the categorical content analysis, with reflections on the ethics of psychoanalysis, on contemporary subjective phenomena of adolescence, whose singular questions permeate the social political field. The results point to the need to foster effective public policies aligned with the demands of adolescents and their families, with a preventive focus on highlighted relational and income vulnerabilities. They also indicate the power of collective activities as an intervention method for strengthening social bonds between them.